A high-strength and lightweight magnesium alloy and preparation method thereof
By adding specific elements and process to the magnesium lithium alloy, a high-strength and lightweight magnesium alloy is formed, which solves the problems of insufficient strength and complex smelting process of magnesium lithium alloy, and achieves high-strength, good toughness and low-cost magnesium alloy preparation.
Patent Information
- Application Number
- CN202211501368.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-28
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2042-11-28
AI Technical Summary
The strength of the existing magnesium lithium alloy is insufficient, making it difficult to replace the application of aluminum alloy on the load-bearing structural parts. At the same time, the traditional vacuum smelting method has problems such as complex equipment, inconvenient operation and inappropriate for large-volume melt smelting.
The components of high-strength and lightweight magnesium alloys include 6.0-15.0% Li, 1.0-4.5% Ni, 1.0-5.0% Cd, 4.0-7.0% Zn, 0.5-5.0% Gd, 0.5-3.0% The total amount of Sr, impurity elements Si, Fe, and Cu is less than 0.02%, and Mg is the balance. The mixture of Li and Mg is carried out by solid-state coating mixing method. Li is heated at low temperature to fully dissolve and diffuse Li to avoid oxidative burning. Then, Mg-Gd and Mg-Sr intermediate alloys are added at high temperature, and process steps such as refining and degassing, semi-continuous casting, homogenization treatment, turning and extrusion are carried out to form a high-strength and lightweight magnesium alloy.
The high strength and good toughness of magnesium lithium alloy are achieved, the room temperature tensile strength reaches 330~380MPa, the yield strength is 200~250MPa, the elongation is 15~40%, and the smelting process is simplified, the production cost is reduced, and it is suitable for industrialization. Mass production.
Smart Images

Figure CN115896570B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal materials and smelting thereof, and in particular to a high-strength and light-weight magnesium alloy and a preparation method thereof. Background Art
[0002] Magnesium-lithium alloy is the lightest metal structural material to date, with a density of 1.35-1.65g / cm 3 It is the best material to solve the problem of lightweight metal components of satellites in the aerospace field. However, the strength of traditional magnesium-lithium alloys is insufficient, significantly lower than that of existing aluminum alloys, and it is difficult to directly replace them in load-bearing structural parts. Therefore, the development of high-strength and tough magnesium-lithium alloys is the development direction of magnesium-lithium alloys.
[0003] In recent years, a lot of research work has been carried out in the field of magnesium-lithium alloys at home and abroad. The existing Mg-Li alloy materials are divided into three categories: single α phase, α+β dual phase, and single β phase. The performance of these three types of alloys is mainly determined by the crystal structure of different phases. Among them, the single α phase alloy has a close-packed hexagonal structure, few slip systems, and poor plasticity; the α+β dual phase alloy has a close-packed hexagonal structure and a cubic structure, and the plasticity is significantly improved, but the strength needs to be further improved; the single β phase alloy has a cubic structure, many slip systems, high plasticity, but low strength. Therefore, how to synergistically improve the strength and toughness of magnesium-lithium alloys is a hot issue in current research.
[0004] In addition, the smelting of magnesium-lithium alloys at home and abroad currently mostly adopts the vacuum melting method. This method has problems such as complex equipment, inconvenient operation, and unsuitability for large-volume melt melting. Therefore, how to simply and conveniently produce magnesium-lithium alloys for industrial large-scale production is also an urgent problem that needs to be solved. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a high-strength and toughness lightweight magnesium alloy with high strength and good toughness, and to provide a simple and easy preparation method of the high-strength and toughness lightweight magnesium alloy that can be industrially mass-produced and has low production cost.
[0006] In order to solve the above technical problems, the present invention provides a high-strength, tough and lightweight magnesium alloy, which comprises, by mass percentage, 6.0-15.0% Li, 1.0-4.5% Ni, 1.0-5.0% Cd, 4.0-7.0% Zn, 0.5-5.0% Gd, 0.5-3.0% Sr, the total amount of impurity elements Si, Fe and Cu is less than 0.02%, and Mg is the balance.
[0007] Furthermore, the atomic numbers of Ni, Zn and Gd satisfy the atomic number ratio of (Ni+Zn) / Gd of 3.0:1 to 7.0:1, and the atomic number ratio of Ni to Zn is 1:1 to 2.2:1.
[0008] The present invention also provides a method for preparing a high-strength and light-weight magnesium alloy, comprising the following steps:
[0009] The raw materials are prepared according to the following percentage by mass: 6.0-15.0% of Li, 1.0-4.5% of Ni, 1.0-5.0% of Cd, 4.0-7.0% of Zn, 0.5-5.0% of Gd, 0.5-3.0% of Sr, the total amount of impurity elements Si, Fe and Cu is less than 0.02%, and Mg is the balance;
[0010] Li is coated with Mg, and placed in a melting furnace at 200-350°C for insulation until Li is dissolved and diffused in Mg, and then the melting furnace is heated to 680-750°C, and Mg-Gd and Mg-Sr master alloys preheated to 300-400°C are added in sequence, and melted and mixed to obtain an alloy melt;
[0011] Refining and degassing the alloy melt;
[0012] The melting furnace temperature is controlled at 690-730°C and the alloy melt is kept warm for 30-90 minutes;
[0013] Semi-continuously casting the alloy melt to obtain an ingot;
[0014] The ingot is homogenized and then air-cooled;
[0015] Turning the air-cooled ingot;
[0016] The turned ingot is heated and then extruded;
[0017] The extruded material is subjected to aging heat treatment and then air-cooled.
[0018] Furthermore, the refining and degassing is carried out using ultrasonically driven flux and inert gas, the ultrasonic power is controlled to be 50-4000W, the processing time is 15-40min, the flux is 500-1000g / min of lithium chloride and lithium fluoride mixed powder, and the inert gas is 0.5-2.0L / min of argon.
[0019] Furthermore, the semi-continuous casting adopts a phase-difference dual-frequency pulse magnetic field to regulate the flow of the alloy melt, the phase difference is controlled to be 60-120°, the current is 80-180A, the high frequency of the dual frequency is 50-200Hz, the low frequency is 10-30Hz, and the pulse duty cycle is 20%-80%.
[0020] Furthermore, the temperature of the ingot homogenization treatment is 280-350° C., and the treatment time is 10-18 hours.
[0021] Furthermore, the ingot after turning is heated to 300-400° C. and then extruded.
[0022] Furthermore, the heating of the ingot after turning adopts gradient heating, and the temperature difference between the head and the tail of the ingot is controlled at 40-70°C.
[0023] Furthermore, the ingot extrusion is performed by using a reverse extruder, the extrusion speed is 1.0-5.0 m / min, the preheating temperature of the extrusion barrel is 250-350° C., and the extrusion ratio is 10-50:1.
[0024] Furthermore, the aging heat treatment temperature of the extruded material is 150-225° C., and the insulation time is 20-50 hours.
[0025] The invention provides a high-strength and tough lightweight magnesium alloy, which has a room temperature tensile strength of 330-380 MPa, a room temperature yield strength of 200-250 MPa, and a room temperature elongation of 15-40%. It has high strength and good toughness at room temperature, is easy to prepare magnesium alloy deformed materials, and is convenient for large-scale preparation.
[0026] In addition, the present invention provides a method for preparing a high-strength and light-weight magnesium alloy. On the one hand, a solid-state coating mixture is used to complete the mixing of industrial pure Mg and Li before smelting, and then heated at a low temperature. Under the premise of ensuring that Mg does not melt, the highly active and low-melting-point Li element can be fully dissolved and diffused into Mg, which can effectively avoid the oxidation and burning of Li. On the other hand, after Li is fully dissolved, the temperature is raised and Mg-Gd and Mg-Sr master alloys are added to prevent the combustion of Mg and Li at high temperatures. These two aspects are conducive to the preparation of alloy melts.
[0027] Moreover, the present invention provides a method for preparing a high-strength, tough and lightweight magnesium alloy, which utilizes the complete solid solution of the Cd element in Mg, utilizes the combination of Ni and Zn elements to react with Mg and Gd to form a phase with good toughness in the high-strength α phase to improve the toughness of the α phase, and forms a phase with high strength in the highly plastic β phase to improve the strength of the β phase, thereby achieving a synergistic improvement in the strength and toughness of the magnesium-lithium alloy.
[0028] At the same time, the present invention provides a method for preparing a high-strength, tough and lightweight magnesium alloy, which has a simple process and uses conventional general-purpose equipment, is easy to transplant and operate, and has low cost. It can solve the problem of difficulty in preparing magnesium-lithium alloys, reduce production costs, and is conducive to expanding the application field of magnesium-lithium alloys. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 A flow chart of a method for preparing a high-strength, tough and lightweight magnesium alloy provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0030] See also Figure 1 An embodiment of the present invention provides a high-strength, tough and lightweight magnesium alloy, which comprises, by mass percentage, 6.0-15.0% Li, 1.0-4.5% Ni, 1.0-5.0% Cd, 4.0-7.0% Zn, 0.5-5.0% Gd, 0.5-3.0% Sr, the total amount of impurity elements Si, Fe and Cu is less than 0.02%, and Mg is the balance.
[0031] The atomic numbers of Ni, Zn and Gd satisfy the atomic number ratio of (Ni+Zn) / Gd of 3.0:1 to 7.0:1, and the atomic number ratio of Ni to Zn is 1:1 to 2.2:1.
[0032] The invention provides a high-strength and tough lightweight magnesium alloy, which has a tensile strength of 330-380 MPa, a yield strength of 200-250 MPa, and an elongation of 15-40% at room temperature, and has high strength and good toughness at room temperature.
[0033] See also Figure 1 The present invention provides a method for preparing a high-strength and light-weight magnesium alloy, comprising the following steps:
[0034] Step 1) Prepare raw materials according to mass percentage, 6.0-15.0% Li, 1.0-4.5% Ni, 1.0-5.0% Cd, 4.0-7.0% Zn, 0.5-5.0% Gd, 0.5-3.0% Sr, the total amount of impurity elements Si, Fe, Cu is less than 0.02%, and Mg is the balance. When adding raw materials, Mg, Li, Cd and Zn are added in the form of industrial pure Mg, pure Li, pure Cd and pure Zn, and Gd and Sr are added in the form of Mg-Gd and Mg-Sr master alloys respectively.
[0035] Step 2) Before smelting, pure Li is coated with industrial pure Mg ingots according to the alloy ratio and compacted. In addition, when coating pure Li with industrial pure Mg ingots, the thickness of the Mg ingots must be ensured to avoid being melted through by Li when Li is heated and melted. Then put it into a smelting furnace preheated to 200-350°C for insulation. After Li is fully dissolved and diffused in Mg, the temperature of the smelting furnace is raised to 680-750°C, and then Mg-Gd and Mg-Sr intermediate alloys preheated to 300-400°C are added in turn. After all the materials are melted, they are fully stirred and mixed to obtain an alloy melt. This variable temperature smelting method can avoid the problem of difficulty in smelting low-melting-point Li with other high-melting-point metals.
[0036] Step 3) refining and degassing the alloy melt to reduce the H content in the alloy melt and prevent the formation of hydrides that may damage the properties of the alloy.
[0037] The refining and degassing treatment is carried out by ultrasonically driving flux and inert gas. The ultrasonic power is controlled at 50-4000W, and the treatment time is controlled at 15-40min. The flux is 500-1000g / min of lithium chloride and lithium fluoride mixed powder, and the inert gas is 0.5-2.0L / min of argon.
[0038] Step 4) After refining and degassing, the alloy melt that has just been refined has defects such as slag inclusions and / or gas, as well as problems such as uneven temperature and composition. Therefore, the temperature of the smelting furnace is controlled at 690-730°C to keep the alloy melt warm for 30-90min. By keeping it still at this temperature for a period of time, the slag inclusions and / or gas can be removed by precipitation or floating, thereby improving the metallurgical quality of the alloy melt. If the temperature of the alloy melt is too low, the viscosity of the alloy melt is large, which is not conducive to the removal of defects therein, and it will also cause difficulties in the subsequent casting of the alloy melt ingots. However, if the temperature of the alloy melt is too high, the magnesium alloy melt is easily oxidized and burned, causing secondary pollution. Therefore, the insulation temperature of the alloy melt is controlled at 690-730°C. At the same time, if the insulation time of the corresponding alloy melt is too short, it is not conducive to the removal of defects in the alloy melt. If the insulation time is too long, it is also easy to cause secondary pollution and increase unnecessary smelting costs. Therefore, the insulation time of the alloy melt is controlled at 30-90min.
[0039] Step 5) semi-continuously casting the alloy melt to obtain an ingot. The semi-continuous casting uses a phase-difference dual-frequency pulse magnetic field to control the flow of the alloy melt, the phase difference is controlled to be 60-120°, the current is 80-180A, the dual-frequency medium-high frequency is 50-200Hz, the low frequency is 10-30Hz, and the pulse duty cycle is 20%-80%.
[0040] Step 6) homogenizing the ingot obtained by semi-continuous casting and then air cooling the ingot, wherein the temperature of the ingot homogenizing treatment is controlled at 280-350° C. and the treatment time is controlled at 10-18 hours.
[0041] Step 7) Since the ingot obtained by semi-continuous casting has many surface defects, which have a great impact on the quality of subsequent product extrusion, the ingot is air-cooled and turned after homogenization to remove the defective parts on the surface of the ingot.
[0042] Step 8) In order to obtain a product with a desired structure, improve the internal organizational structure of the product, and enhance the performance of the product, the turned ingot is heated and then extruded.
[0043] The ingot after turning is heated to 300-400°C before extrusion. The ingot after turning is heated by gradient heating, and the temperature difference between the head and the tail of the ingot is controlled at 40-70°C.
[0044] The ingot extrusion is carried out by using a reverse extruder, the extrusion speed is controlled at 1.0-5.0 m / min, the preheating temperature of the extrusion barrel is controlled at 250-350°C, and the extrusion ratio is 10-50:1.
[0045] Step 9) subjecting the extruded material to aging heat treatment and then air cooling, wherein the aging heat treatment temperature of the extruded material is 150-225° C. and the holding time is 20-50 hours.
[0046] The following is a further description of a method for preparing a high-strength and light-weight magnesium alloy provided by the present invention through an embodiment. It should be understood that the embodiments of the present invention are used to illustrate the present invention rather than to limit the present invention. Simple improvements made to the present invention according to the essence of the present invention all fall within the scope of protection claimed by the present invention.
[0047] In the following embodiments of the present invention, Mg, Li, Cd and Zn are added in the form of industrial pure Mg, pure Li, pure Cd and pure Zn, and Gd and Sr are added in the form of Mg-25 (or 50)% Gd and Mg-25% Sr master alloys, respectively. That is, the mass percentage of Gd in the Mg-Gd master alloy is 25% or 50%, and the mass percentage of Sr in the Mg-Sr master alloy is 25%.
[0048] Example 1
[0049] The composition (mass percentage) of the alloy is: 8.0% Li, 3.0% Ni, 3.0% Cd, 4.0% Zn, 1.0% Gd, 0.5% Sr, the total amount of impurity elements Si, Fe and Cu is less than 0.02%, and Mg is the balance.
[0050] According to the above ingredients, a total of 80 kg of corresponding metal ingots and intermediate alloys are weighed out. Before smelting, pure Li is coated with the prepared industrial pure Mg ingot and compacted, and then placed in a smelting furnace preheated to 250° C. for insulation. After Li is fully dissolved and diffused in Mg, the furnace temperature is raised to 720° C. and the prepared preheated Mg-25% Gd and Mg-25% Sr intermediate alloys are added in sequence. After all the materials are melted, they are fully stirred and mixed. After the alloy is fully melted, the melt is subjected to ultrasonically driven flux and inert gas refining and degassing treatment, with an ultrasonic power of 500 W and a treatment time of 20 min. The flux is 500 g / min of lithium chloride and lithium fluoride mixed powder, and the inert gas is 0.5 L / min. After that, the melting furnace is controlled at 700℃ for insulation and standing for 60 minutes, and then semi-continuous casting is carried out. A dual-frequency pulse magnetic field with a phase difference of 90°, a current of 100A, a dual-frequency medium and high frequency range of 50Hz, a low frequency of 30Hz, and a pulse duty cycle range of 40% is used to stir the melt and solidify it to prepare an ingot. The semi-continuously cast ingot is kept at 300℃ for 12 hours, homogenized, air-cooled, and then turned. The ingot after turning is heated to about 350℃, and the temperature difference between the head and tail of the ingot is ensured to be 50℃. It is extruded by a reverse extruder at an extrusion speed of 2.0m / min, an extrusion barrel temperature of 300℃, and an extrusion ratio of 20; the extruded material is kept at 150℃ for 35 hours for aging treatment.
[0051] The material prepared by the above process was processed into a standard tensile specimen according to the national standard GB / T228-2010, and the tensile performance test was carried out on an Instron 8032 tensile machine.
[0052] The tensile properties of the alloy obtained in this embodiment are as follows: the tensile strength at room temperature is 351 MPa, the yield strength at room temperature is 233 MPa, and the elongation at room temperature is 24.5%.
[0053] Example 2
[0054] The composition (mass percentage) of the alloy is: 10.0% Li, 1.0% Ni, 3.0% Cd, 6.0% Zn, 2.0% Gd, 0.5% Sr, the total amount of impurity elements Si, Fe and Cu is less than 0.02%, and Mg is the balance.
[0055] According to the above ingredients, a total of 120 kg of corresponding metal ingots and intermediate alloys are weighed out. Before smelting, pure Li is coated with the prepared industrial pure Mg ingot and compacted, and then placed in a smelting furnace preheated to 300° C. for insulation. After Li is fully dissolved and diffused in Mg, the furnace temperature is raised to 700° C. and the prepared preheated Mg-25% Gd and Mg-25% Sr intermediate alloys are added in sequence. After all the materials are melted, they are fully stirred and mixed. After the alloy is fully melted, the melt is subjected to ultrasonically driven flux and inert gas refining and degassing treatment, with an ultrasonic power of 1000 W and a treatment time of 30 min. The flux is 600 g / min of lithium chloride and lithium fluoride mixed powder, and the inert gas is 1.0 L / min. After that, the melting furnace is controlled at 720℃ for insulation and standing for 60 minutes, and then semi-continuous casting is carried out. A dual-frequency pulse magnetic field with a phase difference of 90°, a current of 120A, a dual-frequency medium and high frequency range of 50Hz, a low frequency of 25Hz, and a pulse duty cycle range of 50% is used to stir the melt and solidify it to prepare an ingot. The semi-continuously cast ingot is kept at 280℃ for 15h, homogenized, air-cooled, and then turned. The ingot after turning is heated to about 350℃, and the temperature difference between the head and tail of the ingot is ensured to be 40℃. It is extruded by a reverse extruder at an extrusion speed of 2.0m / min, an extrusion barrel temperature of 300℃, and an extrusion ratio of 17; the extruded material is kept at 170℃ for 30h for aging treatment.
[0056] The material prepared by the above process was processed into a standard tensile specimen according to the national standard GB / T228-2010, and the tensile property test was carried out on an Instron 8032 tensile machine.
[0057] The tensile properties of the alloy obtained in this embodiment are as follows: the tensile strength at room temperature is 335 MPa, the yield strength at room temperature is 224 MPa, and the elongation at room temperature is 22.5%.
[0058] Example 3
[0059] The composition (mass percentage) of the alloy is: 9.0% Li, 3.0% Ni, 2.0% Cd, 3.0% Zn, 1.5% Gd, 1.0% Sr, the total amount of impurity elements Si, Fe and Cu is less than 0.02%, and Mg is the balance.
[0060] According to the above ingredients, a total of 20 kg of corresponding metal ingots and intermediate alloys are weighed out. Before smelting, pure Li is coated with the prepared industrial pure Mg ingot and compacted, and then placed in a smelting furnace preheated to 280° C. for insulation. After Li is fully dissolved and diffused in Mg, the furnace temperature is raised to 710° C. and the prepared preheated Mg-25% Gd and Mg-25% Sr intermediate alloys are added in sequence. After all the materials are melted, they are fully stirred and mixed. After the alloy is fully melted, the melt is subjected to ultrasonically driven flux and inert gas refining and degassing treatment, with an ultrasonic power of 400 W and a treatment time of 15 min. The flux is 500 g / min of lithium chloride and lithium fluoride mixed powder, and the inert gas is 0.5 L / min. After that, the melting furnace is controlled at 700℃ for insulation and standing for 30 minutes, and then semi-continuous casting is carried out. A dual-frequency pulse magnetic field with a phase difference of 100°, a current of 80A, a dual-frequency medium and high frequency range of 80Hz, a low frequency of 30Hz, and a pulse duty cycle range of 80% is used to stir the melt and solidify it to prepare an ingot. The semi-continuously cast ingot is kept at 280℃ for 10 hours, homogenized, air-cooled, and then turned. The ingot after turning is heated to about 350℃, and the temperature difference between the head and the tail of the ingot is ensured to be 50℃. It is extruded by a reverse extruder at an extrusion speed of 2.5m / min, an extrusion barrel temperature of 350℃, and an extrusion ratio of 25; the extruded material is kept at 200℃ for 20 hours for aging treatment.
[0061] The material prepared by the above process was processed into a standard tensile specimen according to the national standard GB / T228-2010, and the tensile performance test was carried out on an Instron 8032 tensile machine.
[0062] The tensile properties of the alloy obtained in this embodiment are: the tensile strength at room temperature is 353 MPa, the yield strength at room temperature is 237 MPa, and the elongation at room temperature is 20.0%.
[0063] Example 4
[0064] The composition (mass percentage) of the alloy is: 13.0% Li, 2.0% Ni, 3.0% Cd, 5.0% Zn, 3.0% Gd, 1.0% Sr, the total amount of impurity elements Si, Fe and Cu is less than 0.02%, and Mg is the balance.
[0065] According to the above ingredients, a total of 300 kg of corresponding metal ingots and intermediate alloys are weighed. Before smelting, pure Li is coated with the prepared industrial pure Mg ingot and compacted. Then, the ingot is placed in a smelting furnace preheated to 300° C. for heat preservation. After Li is fully dissolved and diffused in Mg, the furnace temperature is raised to 730° C. and the prepared preheated Mg-25% Gd and Mg-25% Sr intermediate alloys are added in sequence. After all the materials are melted, they are fully stirred and mixed. After the alloy is fully melted, the melt is subjected to ultrasonically driven flux and inert gas refining and degassing treatment, with an ultrasonic power of 2000 W and a treatment time of 30 min. The flux is 800 g / min of lithium chloride and lithium fluoride mixed powder, and the inert gas is 1.5 L / min. After that, the melting furnace is controlled at 730℃ for insulation and standing for 30 minutes, and then semi-continuous casting is carried out. A dual-frequency pulse magnetic field with a phase difference of 90°, a current of 150A, a dual-frequency medium and high frequency range of 100Hz, a low frequency of 15Hz, and a pulse duty cycle range of 80% is used to stir the melt and solidify it to prepare an ingot. The semi-continuously cast ingot is kept at 330℃ for 15h, homogenized, air-cooled, and then turned. The ingot after turning is heated to about 350℃, and the temperature difference between the head and tail of the ingot is ensured to be 60℃. It is extruded by a reverse extruder at an extrusion speed of 3.0m / min, an extrusion barrel temperature of 330℃, and an extrusion ratio of 18; the extruded material is kept at 160℃ for 35h for aging treatment.
[0066] The material prepared by the above process was processed into a standard tensile specimen according to the national standard GB / T228-2010, and the tensile performance test was carried out on an Instron 8032 tensile machine.
[0067] The tensile properties of the alloy obtained in this embodiment are as follows: the tensile strength at room temperature is 311 MPa, the yield strength at room temperature is 223 MPa, and the elongation at room temperature is 34.5%.
[0068] Example 5
[0069] The composition (mass percentage) of the alloy is: 6.0% Li, 1.0% Ni, 1.0% Cd, 6.0% Zn, 2.0% Gd, 2.0% Sr, the total amount of impurity elements Si, Fe and Cu is less than 0.02%, and Mg is the balance.
[0070] According to the above ingredients, a total of 200 kg of corresponding metal ingots and intermediate alloys are weighed. Before smelting, pure Li is coated with the prepared industrial pure Mg ingot and compacted, and then placed in a smelting furnace preheated to 280° C. for insulation. After Li is fully dissolved and diffused in Mg, the furnace temperature is raised to 7350° C. and the prepared preheated Mg-25% Gd and Mg-25% Sr intermediate alloys are added in sequence. After all the materials are melted, they are fully stirred and mixed. After the alloy is fully melted, the melt is subjected to ultrasonically driven flux and inert gas refining and degassing treatment, with an ultrasonic power of 1500 W and a treatment time of 25 min. The flux is 500 g / min of lithium chloride and lithium fluoride mixed powder, and the inert gas is 1.0 L / min. After that, the melting furnace is controlled at 720℃ for insulation and standing for 40 minutes, and then semi-continuous casting is carried out. A dual-frequency pulse magnetic field with a phase difference of 90°, a current of 130A, a dual-frequency medium and high frequency range of 90Hz, a low frequency of 20Hz, and a pulse duty cycle range of 80% is used to stir the melt and solidify it to prepare an ingot. The semi-continuously cast ingot is kept at 320℃ for 18 hours, homogenized, air-cooled, and then turned. The ingot after turning is heated to about 300℃, and the temperature difference between the head and tail of the ingot is ensured to be 40℃. It is extruded by a reverse extruder at an extrusion speed of 2.5m / min, an extrusion barrel temperature of 250℃, and an extrusion ratio of 27; the extruded material is kept at 150℃ for 45 hours for aging treatment.
[0071] The material prepared by the above process was processed into a standard tensile specimen according to the national standard GB / T228-2010, and the tensile property test was carried out on an Instron 8032 tensile machine.
[0072] The tensile properties of the alloy obtained in this embodiment are as follows: the tensile strength at room temperature is 367 MPa, the yield strength at room temperature is 243 MPa, and the elongation at room temperature is 16.5%.
[0073] It can be seen from the above embodiments that the method for preparing a high-strength and tough lightweight magnesium alloy provided by the present invention can produce a Mg-Zn-Gd-Zr alloy having high strength at room temperature and very high elongation at medium and low temperatures.
[0074] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a high-strength and light-weight magnesium alloy, characterized in that: The steps include: The raw materials are prepared according to the composition ratio, and the components include, by mass percentage, 6.0-15.0% Li, 1.0-4.5% Ni, 1.0-5.0% Cd, 4.0-7.0% Zn, 0.5-5.0% Gd, 0.5-3.0% Sr, the total amount of impurity elements Si, Fe, and Cu is less than 0.02%, and Mg is the balance; wherein the number of atoms of Ni, Zn, and Gd satisfies the atomic number ratio of (Ni+Zn) / Gd of 3.0:1-7.0:1, and the atomic number ratio of Ni to Zn is 1:1-2.2:1; Li is coated with Mg, and placed in a melting furnace at 200-350°C for insulation until Li is dissolved and diffused in Mg, and then the melting furnace is heated to 680-750°C, and Mg-Gd and Mg-Sr master alloys preheated to 300-400°C are added in sequence, and melted and mixed to obtain an alloy melt; Refining and degassing the alloy melt; The melting furnace temperature is controlled at 690-730°C and the alloy melt is kept warm for 30-90 minutes; Semi-continuously casting the alloy melt to obtain an ingot; The ingot is homogenized and then air-cooled; Turning the air-cooled ingot; The turned ingot is heated and then extruded; The extruded material is subjected to aging heat treatment and then air-cooled.
2. The method for preparing a high-strength and light-weight magnesium alloy according to claim 1, characterized in that: The refining and degassing is carried out by ultrasonically driven flux and inert gas, the ultrasonic power is controlled to be 50-4000W, the processing time is 15-40min, the flux is 500-1000g / min of lithium chloride and lithium fluoride mixed powder, and the inert gas is 0.5-2.0L / min of argon.
3. The method for preparing a high-strength and light-weight magnesium alloy according to claim 1, characterized in that: The semi-continuous casting adopts a phase-difference dual-frequency pulse magnetic field to regulate the flow of the alloy melt, the phase difference is controlled to be 60-120°, the current is 80-180A, the dual-frequency medium-high frequency is 50-200Hz, the low frequency is 10-30Hz, and the pulse duty cycle is 20%-80%.
4. The method for preparing a high-strength and light-weight magnesium alloy according to claim 1, characterized in that: The temperature of the ingot homogenization treatment is 280-350° C., and the treatment time is 10-18 hours.
5. The method for preparing a high-strength and light-weight magnesium alloy according to claim 1, characterized in that: The turned ingot is heated to 300-400° C. and then extruded.
6. The method for preparing a high-strength and light-weight magnesium alloy according to claim 1, characterized in that: The heating of the ingot after turning adopts gradient heating, and the temperature difference between the head and the tail of the ingot is controlled at 40-70°C.
7. The method for preparing a high-strength and light-weight magnesium alloy according to claim 1, characterized in that: The ingot extrusion is carried out by using a reverse extruder, the extrusion speed is 1.0-5.0 m / min, the preheating temperature of the extrusion barrel is 250-350° C., and the extrusion ratio is 10-50:
1.
8. The method for preparing a high-strength and light-weight magnesium alloy according to claim 1, characterized in that: The aging heat treatment temperature of the extruded material is 150-225° C., and the insulation time is 20-50 hours.
Citation Information
Patent Citations
Preparation method of magnesium-lithium alloy with reinforced LPSO (long-period stacking ordered) structure
CN107630157A
Multi-element microalloyed biphase magnesium-lithium alloy and preparation method thereof
CN110029254A
Magnesium-lithium alloy foil and preparation method and application thereof
CN111004951A
High-plasticity rapidly-degradable Mg-Li-Gd-Ni alloy and preparation method thereof
CN114411029A